Challenges of franchising towards its organizational performance at Shah Alam / Muhammad Rizal Roslee - Roslee, Muhammad Rizal (Faculty of Business and Management, 2016)
This research aims to investigate the franchising challenges towards organization performance in Shah Alam. Franchising can be described as a practice of using a business models and brand names and using it right for a period of time. It's also known as Anglo-French derived from French, meaning fee and is used both as a noun and as a verb (Dictionary, 2001). In this current globalization era, franchising is a command business throughout the market as it might bring better profit and easier to manage. Each franchise must compete with each other and create competitive advantage to in striving for success. This project paper covers the study of challenges on managing a franchise towards its performance in Shah Alam. A franchisee need to be aware of its changes in variables that commonly are competitions, area and experiences. This independent variable will lead towards the organizational performance of the franchise. As many franchises nowadays, they are unable to succeed towards its performance when facing many problems or challenges occur whether internally or externally. Pearson correlation coefficient is used to measure independent variables and the dependent variable through its strength of relationship. The data collected for this research paper through questionnaires that are distributed to the manager’s or supervisors of franchising in Shah Alam area.